CAFFE VISITOR COUNTER BASED ANDROID ULTRASONIC SENSOR AND BLUETOOTH - Lestari, Dewi; Yuniarti, Elvan (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2025)
In the cafe industry, real-time visitor monitoring is a critical challenge for operational optimization. This study develops a visitor counting system based on ultrasonic sensors and Bluetooth communication, designed for cafes in Indonesia. The ultrasonic sensor detects the presence of visitors based on distance, while the data is sent to an Android application via the HC-05 Bluetooth module. With an experimental approach, the system was tested in different scenarios (individual visitors, groups, and walking speed) to evaluate the accuracy. The results show that the sensor is able to identify visitors at a distance of ≤15 cm. Bluetooth integration ensures stable data transmission with a maximum distance of 10 meters. This system provides a cost-effective wireless solution for cafe owners, although further research is needed to overcome the drawbacks in dynamic scenarios.